UPAYA PEMERINTAH KABUPATEN OGAN KOMERING ULU SELATAN DALAM PEMBERDAYAAN MASYARAKAT (Studi Kasus Badan Pemberdayaan Masyarakat dan Pemerintah Desa) - Ikang Putra Anggara (SOSIALITA, 2018)
One aspect that is still the main focus of attention in the process of administering government is the strong demand for social empowerment that has not yet found the best solution. Especially for people in rural and remote areas, attention and partisanship of the government requires strategies and methods that are comprehensive and unusual or only modest. This research was conducted in August to December 2016, using a qualitative descriptive research method involving 4 (four) informants. Data collection techniques through observation, interviews, and documentation. Data is analyzed through data reduction, data presentation and verification. The indicators used to examine the Efforts of the OKU Selatan Regency Government in Empowering Rural Communities are enabling, empowering and protection. The results of the study show that empowerment to rural communities, especially the outermost villages and farthest from the reach of the district government, is still not in line with ideal expectations. Especially if viewed from 3 (three) main indicators, namely enabling or enabling a conducive atmosphere for the development and growth of community welfare, empowering or translating into reinforcement where people are encouraged and encouraged to be stronger and more empowered, and provide protection so that people do not experience discrimination and oppression from other groups or forces.